Cardiac failure secondary to hypocalcemia - Namazi, Mohammad Hasan; Khaheshi, Isa; Charkhkar, Mahsa; Esmaeeli, Shooka; Haybar, Habib (International Journal of Cardiovascular Practice, 2016)
Hypocalcemic cardiomyopathy due to hypoparathyroidism is a very atypical and rare circumstance, which is usually intractable to conventional therapy for cardiac failure, but responds satisfactorily to restoration of normocalcemia.We describe a young woman who developed clinical signs of hypocalcemia due to hypoparathyroidism, reduced left ventricular ejection fraction and polymorphic ventricular tachycardia as consequences of hypocalcemia.This case underscores the importance of biochemical abnormalities like hypocalcemia as a rare cause of secondary cardiomyopathy and emphasizes on the need for effective and immediate treatment of hypocalcemia and its related causes.